Cell and scaffold surface engineering to enhance cell migration and tissue regeneration. Issue 1 (March 2014) - Maerz, Tristan; Mu, Richard; Baker, Kevin C.
Abstract : The principles of surface engineering can be applied to cells and biomaterial scaffolds in efforts to treat disease, disorder, infection and injury. Although the body's endogenous response to some injuries is limited, cell-based approaches exploiting native physiology, namely, through the use of gene therapy or cell surface receptors hold significant promise in treating injured or diseased tissues. Shifting binding affinities of native receptors, causing expression of non-native receptors, or binding synthetic receptors onto the surfaces of cells are the techniques that increase cellular targeting, migration and engraftment. Scaffold modification techniques that increase a scaffold's bioactivity by providing signaling factors to endogenous cells can be used to elicit a desired response from an otherwise inert polymer. This review summarizes the endogenous homing and targeting response of leukocytes and stem cells to provide context for subsequent sections outlining existing ways of surface-modifying cells and biomaterials.